Preparação e caracterização do compósito PVDF/Pani com partículas de níquel - Dias, Gabriel Da Cruz [UNESP]; De Paula, Fernando Rogério [UNESP]; Malmonge, José Antonio [UNESP]; Malmonge, Luiz Francisco [UNESP] (FapUNIFESP (SciELO), 2017)
In this work nickel particles were incorporated by physically mixing of resulting powder blends of PVDF/Pani, obtained by chemical synthesis. Homogeneous films were obtained by hot pressing at 180 °C. From the results could be noted favorable and unfavorable changes in the properties of composites after incorporation and how this become dependent of the incorporation. The results of diffraction showed the characteristic peaks of both the α phase of the polymer matrix and the nickel particles, and with thermal analysis, no change in the conformational structure and configurational. Even with a good thermal stability incorporating, indicates that besides the presence of the conducting polymer as the increase of particles are harmful to the final mechanical properties of the sample. Micrographs showed particles dispersed throughout the film and determinants to electrical conductivity values and achieving a magnetic phase.
Preparation and characterization the composite PVDF/Pani with nickel particles
Keywords: Composite; Magnetic property; Nickel; Poly (vinylidene fluoride); Polyaniline